Assessing the Mediating Role of Competitive Advantage: The Influence of Innovation Capabilities and Strategic Flexibility on Firm Performance in East Java’s F&B Industry Post COVID-19 - Gunawan, Clara Angelia; Ongkowijoyo, Gracia (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study investigates the mediating role of competitive advantage in the innovation capability and strategic flexibility-firm performance link, in regard to the food and beverage SMEs of East Java, post-COVID-19. This research will seek to explain how these two factors contribute to firm performance by having competitive advantage as a mediating variable. Data were collected from 107 respondents who underwent quantitative analysis. The results showed that innovation capability significantly and directly affects competitive advantage and firm performance, while strategic flexibility affects firm performance only significantly through the mediation of competitive advantage, noting its indirect role. Again, this research points to the enhancement of innovation capabilities as an important way to sustain competitive advantages; hence, a recommendation goes to SMEs in East Java for strategizing to become adaptable. The findings form a helpful indication for the SME managers on how to develop long-term performance in the dynamic business environment.